Bài 72 trang 154 SGK Đại số 10 nâng cao


    Giải các bất phương trình saua) \(\sqrt {{x^2} + 6x + 8}  \le 2x + 3\)b) \({{2x - 4} \over {\sqrt {{x^2} - 3x - 10} }} > 1\)c) \(6\sqrt {(x - 2)(x - 32)}  \le {x^2} - 34x + 48\)Đáp ána)Áp dụng:\(\sqrt A = B \Leftrightarrow \left\{ \matrix{ A...

    Giải các bất phương trình sau

    a) \(\sqrt {{x^2} + 6x + 8}  \le 2x + 3\)

    b) \({{2x – 4} \over {\sqrt {{x^2} – 3x – 10} }} > 1\)

    c) \(6\sqrt {(x – 2)(x – 32)}  \le {x^2} – 34x + 48\)

    Đáp án

    a)

    Áp dụng:

    \(\sqrt A = B \Leftrightarrow \left\{ \matrix{
    A \ge 0 \hfill \cr
    B \ge 0 \hfill \cr
    A \le {B^2} \hfill \cr} \right.\)

    Ta có:

    \(\eqalign{
    & \sqrt {{x^2} + 6x + 8} \le 2x + 3 \cr&\Leftrightarrow \left\{ \matrix{
    {x^2} + 6x + 8 \ge 0 \hfill \cr
    2x + 3 \ge 0 \hfill \cr
    {x^2} + 6x + 8 \le {(2x + 3)^2} \hfill \cr} \right. \cr
    & \Leftrightarrow \left\{ \matrix{
    \left[ \matrix{
    x \le – 4 \hfill \cr
    x \ge – 2 \hfill \cr} \right. \hfill \cr
    x \ge – {3 \over 2} \hfill \cr
    3{x^2} + 6x + 1 \ge 0 \hfill \cr} \right. \cr&\Leftrightarrow \left\{ \matrix{
    x \ge – {3 \over 2} \hfill \cr
    \left[ \matrix{
    x \le {{ – 3 – \sqrt 6 } \over 3} \hfill \cr
    x \ge {{ – 3 + \sqrt 6 } \over 3} \hfill \cr} \right. \hfill \cr} \right. \Leftrightarrow x \ge {{\sqrt 6 } \over 3} – 1 \cr} \)

    Vậy \(S = {\rm{[}}{{\sqrt 6 } \over 3} – 1, + \infty )\)

    b) Ta có:

    \(\eqalign{
    & {{2x – 4} \over {\sqrt {{x^2} – 3x – 10} }} > 1\cr& \Leftrightarrow \left\{ \matrix{
    {x^2} – 3x – 10 > 0 \hfill \cr
    \sqrt {{x^2} – 3x – 10} < 2x – 4 \hfill \cr} \right. \cr
    & \Leftrightarrow \left\{ \matrix{
    {x^2} – 3x – 10 > 0 \hfill \cr
    2x – 4 > 0 \hfill \cr
    {x^2} – 3x – 10 < {(2x – 4)^2} \hfill \cr} \right. \cr&\Leftrightarrow \left\{ \matrix{
    \left[ \matrix{
    x < – 2 \hfill \cr
    x > 5 \hfill \cr} \right. \hfill \cr
    x > 2 \hfill \cr
    3{x^2} – 13x + 26 > 0\,\,(\forall x) \hfill \cr} \right. \Leftrightarrow x > 5 \cr} \)

    Vậy \(S = (5, +∞)\)

    c) Đặt \(y = \sqrt {(x – 2)(x – 32)}  = \sqrt {{x^2} – 34x + 64} \,\,\,(y \ge 0)\)

    ⇒ x2 – 34x = y2 – 64

    Ta có bất phương trình:

    6y ≤ y– 16 ⇔ y2 – 6y – 16 ≥ 0 ⇔ y ≤ 2 hoặc y ≥ 8

    Với điều kiện y ≥ 0, ta có:

    y ≥ 8 ⇔  x2 – 34x + 64 ≥ 64 ⇔  x2 – 34x ≥ 0

    ⇔  x ≤ 0 hoặc x ≥ 34

    Vậy \(S = (-∞, 0] ∪ [34, +∞)\)